Differences in handgrip strength and tooth loss between cognitively normal and impaired elderly: cross-sectional study - Syamila, Rahmi Hasna; Sari, Kartika Indah; Balafif, Felisha Febriane; Ong, Paulus Anam; Gondowidjojo, Yolanda Dwiutami (Padjadjaran Journal of Dentistry, 2025)
Introduction: The aging process in elderly individuals triggers changes in the brain that can lead to a decline in cognitive function, impacting quality of life. Age-related physiological changes affect the muscles around the oral cavity and the musculoskeletal system. These changes manifest as a decrease in the mass and strength of the chewing muscles. Tooth loss further exacerbates the ability to chew. This study aims to analyze differences in handgrip strength and tooth loss between cognitively normal and impaired elderly. Methods: Observational analytic with cross-sectional design using the Mann-Whitney comparative significance test and independent sample t-test with a significance level of p<0.05 was conducted. A purposive sampling technique was applied to a population residing in Dago Village, Bandung. The inclusion criteria included elderly individuals aged ≥60 years, both male and female, able to communicate effectively, and willing to participate in the study by signing an informed consent form. Cognitive function was assessed through interviews using the Mini Mental State Examination (MMSE), along with an examination of the number of missing teeth and hand grip strength measured with the Electronic Hand Dynamometer (Camry EH101). Analyzed data used the Mann–Whitney test. Results: A total of 34 subjects met the inclusion criteria from the total population of 71 older adults examined. The independent sample t-test for handgrip strength showed that elderly individuals with cognitive impairment had weaker handgrip strength (mean=14.250, SD=5.0285) compared to cognitively normal individuals (mean=22.281, SD=6.0204), with a p-value of 0.0001 (p<0.05). The Mann–Whitney test results for tooth loss indicated that elderly individuals with cognitive impairment experienced greater tooth loss (range=11–32 teeth, mean=20.78) compared to cognitively normal individuals (range=0–10 teeth, mean=13.81), with a p-value of 0.041 (p<0.05). Conclusion: There are differences in hand grip strength and tooth loss were found between cognitively normal and impaired elderly.